Impact Top Management Education Background And Innovation on Firm Performance - Pane, Zulfikar Ikhsan; Bonnie Mindosa; Taofic Rachmat (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
Current business developments require companies to sustain made innovations and supported from top-level management. For this reason, this study tries to examine role director educational background and innovation on firms performance as well as proposed new innovation calculation as a research novelty. Using 56 observations from 2021 - 2023 in companies that report ESG risk score, it is concluded that innovation and directors with engineering / technology education background improve firms performance. This study also proves that presence of these directors strengthens the effect of innovation on firms performance. Last, novelty of innovation calculation is proven better than previous formula.